المعضلة الأمنية الحوثية وتأثيراتها على المنطقة - العربية والدولية 2011-2018 - بلخير, سعاد (جامعة المسيلة محمد بوضساف, 2019)
يشهد اليمن أزمات أمنية خطيرة، تهدد الدولة بالانهيار وتسمح بالفوضى وعدم الاستقرار في البلاد، وبداية من 1122 تاريخ اندلاع ما يعرف بالربيع العربي الذي اجتاح المنطقة العربية ابتداء من تونس ومصر وليبيا وسوريا، وكانت اليمن مسرحا لها وبالإضافة إلى التحديات الأمنية المتمثلة في الحراك الجنوبي وتنظيم القاعدة تبرز الظاهرة الحوثية كأهم وأعقد المعضلات الأمنية التي تواجه الدولة اليمنية، وتطل بتداعياتها على المنطقة العربية والدولية، ومن أبرز هذه التداعيات نجملها في النقاط التالية: مست جوهر الوحدة اليمنية المذهبية والترابية.  ضاعفت من الأزمات الاجتماعية والاقتصادية لليمن.  وضعت قضية الصراع اليمني محل التدويل والتدخل الأجنبي.  شكلت تهديد أمني واقتصادي لدول مجلس التعاون الخليجي.  أصبحت مصدر تهديد أمني على التجارة والاقتصاد العالمين.  Abstract Yemen is witnessing serious security crises threatening the state of collapse and allowing chaos and instability in the country. Beginning in 2011, the date of the outbreak of the Arab Spring, which swept through the Arab region starting with Tunisia, Egypt, Libya and Syria. Yemen was a theater. In addition to the security challenges represented by the Southern Movement and Al-Qaeda, As the most important and complex security dilemmas facing the Yemeni state, and the implications of the repercussions on the Arab and international region, and the most prominent of these repercussions are summarized in the following points: • The essence of Yemen's sectarian and territorial unity. • Increased social and economic crises in Yemen. • The issue of the Yemeni conflict has been the subject of internationalization and foreign intervention. • constituted a security and economic threat to the GCC countries. • Has become a source of security threat to global trade and economy
Keywords: اليمن -المعضلىة الحوثية -2011-2018-العلاقات الدولية